O repertório ocupacional após diagnóstico de HIV - Erica Guimarães Gontijo (2021)
Changes related to chronic disease and stigmatizing, such as infection by the human immunodeficiency virus (HIV), cause changes in the occupational repertoire. This dissertation should aim to verify how the HIV diagnosis interferes in the occupational repertoire. For this it was necessary to characterize people diagnosed with HIV in relation to demographic data, clinical data and occupational repertoire; identify changes in the occupational repertoire before and after diagnosis; verify the impact of physical, cognitive and psychological changes on occupational repertoire. Data collection was performed using a structured online questionnaire to collect demographic and clinical data, with the ACTIVITY CARD SORT BRASIL (ACS) assessment being inserted. This is a cliente-centred, occupation-based assessment, just like the Canadian Occupational Performance Measure and Occupational Roles Identification List. However, the ACS is the only instrument validated in Brazil that assesses participation and engagement in occupations and has a list of 83 activities, which culturally make up the occupational repertoire of the Brazilian population. This instrument provides information about which activities were interrupted or there was a decrease in participation, and it is possible to show changes in the occupational repertoire. The sample of this research consisted of 48 participants, all with an undetectable viral load, who lived in Minas Gerias, underwent medical and drug treatment and participated in an online support group. Most participants were male, aged between 23 and 69 years, with a predominance of high education and treatment time from 1.5 to 32 years. A minority of the sample presented psychological, physical or cognitive alterations. Significant changes related to instrumental and high demand leisure activities after HIV diagnosis were observed, with the inclusion of activities such as Walking, running, Gardening, "yoga, pilates or tai chi chuan", "care with medication" and "go to the doctor or therapy”. The average preserved percentage of activities that make up the occupational repertoire of this sample was 93%, and it was found that participants with reports of cognitive impairment, fatigue, visual impairment, pain or weakness in the lower limbs were more likely to experience changes in the occupational repertoire of the that PLHIV without reporting. It is concluded that the restructuring of the new occupational pattern after HIV diagnosis, as well as social support from the treatment team and the online support group, may have contributed to a significant change in the occupational repertoire in instrumental and high-demand leisure activities.